Inserção profissional na rede de ensino do Município de Guarulhos de alunas egressas do curso de Pedagogia da Universidade Federal de São Paulo- Campus Guarulhos - Fernandes, Ana Alice Izidorio [UNIFESP] (2019)
The objective of this work is to investigate the course of five new teachers, all graduates of the Pedagogy course at the Federal University of Sao Paulo, Guarulhos campus. They entered the teaching network of Guarulhos following an entry exam of “Teacher of Basic Education (nº 01 / 2016-SAM 01)” and homologated in the year 2017. We sought to identify the process of insertion of female students by examining narratives; the encountered difficulties and discoveries at the beginning of the teaching career; If the participating students identified in their research, whether the initial training received at UNIFESP was relevant for their understanding for teaching work. Huberman (1995) considers the beginning of a teaching career as more or less the same for all. For Marcelo (1999), Imbernón (2011) and Gariglio (2016) professional insertion is a stage of professional teacher development. We understand career development as a continuum. We work with this perspective from the beginning throughout the whole teaching career. The quality research carried out was about 24 new teachers of which 5 were females from the UNIFESP Guarulhos Campus. The used methodological tool was a survey, developed through the Google online questionnaire that was sent to all female teachers. Five reflective diaries of only pedagogy course teachers were used (ZABALZA, 2004). The diaries are personal documents that express the teachers’ thoughts and we are able to share these expressions of teaching activity. For the produced analysis of the data through the diaries, we establish categories posteriori from the prose analysis (ANDRÉ, 1983). We identify two categories of obstacles and achievements. When analyzing the data in the light of the referential, we conclude that the Unifesp – Guarulhos campus undergraduate teachers present in their diaries specific questions about the beginning of the teaching career such as the transition between “being a student” and “being a teacher, the "shock of reality" and "discovery" (HUBERMAN, 1995) and recognize the contributions of the training received at Unifesp - Guarulhos campus as a good course. The initial exercise of reflection - action - reflection (FREIRE, 2016) favored their professional development.